Development of Rural Tourism after the Coronavirus Pandemic - MUGAUINA, Raikhan; REY, Inna Yuryevna; SABIROVA, Rysty; RAKHISHEVA, Aida Bekarysovna; BERSTEMBAYEVA, Rysty; BEKETOVA, Kamar Nazarbekovna; ZHANSAGIMOVA, Ayagoz (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2021)
The travel and tourism industry around the world have been hit by the pandemic for various reasons, which are described in more detail in this article. The tourism sector is experiencing a significant and unexpected decline in demand due to the spread of the coronavirus pandemic. In such conditions, tour operators, travel agents, carriers and other participants in the tourist services market suffered serious losses. Airlines are now experiencing the largest crisis in history. And if state-owned companies can hope for the support of the government, then private ones have the worst, some of the travel companies will go bankrupt altogether. The situation associated with COVID-19 requires a new approach from the tourism business, strengthening sanitary and epidemiological security measures. The search for solutions to overcome the crisis in the tourism sector is an acute problem throughout the civilized world; the Government is faced with the task of preparing an action program and developing plans in case of recurrence of similar threats in the future. According to the authors, it is necessary to intensively engage in the development of domestic tourism, and in particular, the sustainable development of rural tourism, since in a pandemic, a ban on entry and exit from the country is prohibited, and the population's love for travel will resume. The country should prepare to receive domestic tourists in accordance with the new rules for receiving tourists. This article contains policies for the development of tourism in some developed countries and focuses on changing the dimension of tourism and its sustainable approach, and also focuses on mutual benefits and non-agricultural activities, i.e. tourism. Agritourism in Kazakhstan has great potential both as a business and as a tool for the development of rural areas. The recovery of the travel and tourism industry will be extremely gradual, and safety concerns for guests and staff should be a top priority for travel and tourism industry stakeholders.